Islamic Entrepreneurship among Single-Parent Teachers in Islamic Boarding Schools: A Model for Strengthening Family Economic Resilience Based on Islamic Values at Pesantren Al-Amien Putri I - Hermanto Halil; Annatul Aini (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the implementation of Islamic entrepreneurship among single-parent teachers at Pesantren Al-Amien Putri I Prenduan as a model for strengthening family economic resilience based on Islamic values. The increasing phenomenon of single-parent families has created complex economic, psychological, and social challenges, particularly for women who carry dual roles as educators and heads of households. In the pesantren context, these challenges are addressed through entrepreneurial practices that are not solely profit-oriented, but also integrate spiritual, moral, and Islamic educational values. This study employed a qualitative approach using a case study design. Data were collected through semi-structured interviews, non-participant observation, and documentation involving single-parent teachers at Pesantren Al-Amien Putri I Prenduan. Data analysis utilized the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing conducted simultaneously. The findings reveal that the implementation of Islamic entrepreneurship is manifested through the development of productive businesses based on pesantren needs, the internalization of the values of ṣidq (honesty), amanah (trustworthiness), responsibility, and an orientation toward barakah (blessing) in economic activities. These entrepreneurial practices not only strengthen family economic resilience but also enhance psychological resilience, women’s independence, and the spiritual resilience of single-parent teachers. Supporting factors include pesantren culture, social support, workplace flexibility, and individual religiosity, while the main challenges involve limited time, business capital constraints, emotional exhaustion, and social stigma. This study formulates the conceptual model of Islamic Edupreneurship for Family Resilience as an integration of economic empowerment, character education, and spiritual strengthening in building pesantren-based family resilience.